Osseous metaplasia of the endometrium: A rare finding in endometrial biopsy (Indian Journal of Case Reports, 2026)
Endometrial osseous metaplasia is a rare benign condition characterized by the presence of bone within the endometrial cavity. It is an uncommon cause of abnormal uterine bleeding and secondary infertility, often following abortion. We report the case of a 28-year-old female presenting with irregular menstrual bleeding after two consecutive abortions. Ultrasonography suggested osseous metaplasia, and an endometrial biopsy was performed. Histopathological examination revealed well-formed bony trabeculae with hematopoietic elements, without evidence of atypia or malignancy, confirming the diagnosis of endometrial osseous metaplasia. This case emphasizes the pivotal role of histopathology in establishing a definitive diagnosis and excluding important differential diagnoses such as retained fetal bone and malignant endometrial lesions.